Can economic development be a moral justification to amend the constitution of Malawi? - Njima, Thokozani Tarisai (KDI School, 2012)
The purpose of this study is to examine critically the prevalent tendency among emerging democracies of justifying a constitutional amendment, which aims at extending incumbent presidents’ constitutionally-defined terms of office, with economic development. The analysis is purely on the basis of moral and constitutional theory of constitutional democracy. From a case study of Malawi’s politics, we learn that a moral imperative, such as economic development, can never morally justify an unethical means.
Thesis(Master) -- KDI School: Master of Public Policy, 2012
Keywords: Democracy--Malawi; Constitutional law--Malawi; Constitutional amendments--Malawi; Emerging democracies, illiberal democracy, constitutional democracy, developmental dictatorship, constitutional amendment, moral justification, economic development